Governança hídrica na região semiárida do Estado de Pernambuco (Brasil): análise da gestão do Comitê da Bacia Hidrográfica do São Francisco - Sidclay Cordeiro Pereira; Hildelano Delanusse Theodoro (Caravelle)
The article aims to understand water governance in the semiarid region of the state of Pernambuco, Brazil, through the analysis of the actions of the representatives of the São Francisco River Basin Committee in the 2016-2020 period. The research made use of published data and information and interviews with members of the Sub-Middle San Francisco Regional Advisory Board. In conclusion it is essential to encourage the participation of subjects in institutional change for good governance.